Dual IL-6 and CTLA-4 blockade regresses pancreatic tumors in a T cell– and CXCR3-dependent manner - Michael Brandon Ware; Maggie Phillips; Christopher McQuinn; Mohammad Y. Zaidi; Hannah M. Knochelmann; Emily Greene; Brian Robinson; Cameron J. Herting; Thomas A. Mace; Zhengjia Chen; Chao Zhang; Matthew R. Farren; et al. (JCI Insight, 2023)
This study aimed to enhance antitumor immune responses to pancreatic cancer via Ab-based blockade of IL-6 and cytotoxic T-lymphocyte–associated protein 4 (CTLA-4). Mice bearing s.c. or orthotopic pancreatic tumors were treated with blocking Abs to IL‑6 and/or CTLA-4. In both tumor models, dual IL-6 and CTLA-4 blockade significantly inhibited tumor growth. Additional investigations revealed that dual therapy induced an overwhelming infiltration of T cells into the tumor as well as changes in CD4+ T cell subsets. Dual blockade therapy elicited CD4+ T cells to secrete increased IFN-γ in vitro. Likewise, in vitro stimulation of pancreatic tumor cells with IFN-γ profoundly increased tumor cell production of CXCR3-specific chemokines, even in the presence of IL-6. In vivo blockade of CXCR3 prevented orthotopic tumor regression in the presence of the combination treatment, demonstrating a dependence on the CXCR3 axis for antitumor efficacy. Both CD4+ and CD8+ T cells were required for the antitumor activity of this combination therapy, as their in vivo depletion via Abs impaired outcomes. These data represent the first report to our knowledge of IL-6 and CTLA‑4 blockade as a means to regress pancreatic tumors with defined operative mechanisms of efficacy.